Integration of Religious Moderation Values in the Islamic Religious Education Learning - Nurul 'Aini, Robi'ul Afif; Zamroji, Muhammad (Tarsib: Jurnal Program Studi PGMI, 2025)
Islamic Religious Education in schools plays a crucial role in integrating religious moderation values to prevent intolerance, which is frequently observed among adolescents aged 14–20. This study employs a qualitative descriptive approach, with data collected through observations, interviews, and document analysis. The research subjects include the school principal, vice principal, and Islamic Religious Education educators. The findings indicate that the religious moderation values integrated into Islamic Religious Education learning include tolerance, balance, harmony, humanism, equality, patriotism (hubbul wathon), mutual respect, forgiveness, cooperation, justice, discipline, and independence. These values are implemented through various approaches and integration strategies in Islamic Religious Education learning. The strategies include the traditional integration strategy, which emphasizes direct advice; the free-choice integration strategy, which allows students to internalize values independently; the reflective strategy, which connects theory with real-life experiences; the transinternal strategy, which emphasizes inner involvement; and the transdisciplinary strategy, which links religious values with other fields of knowledge. This study highlights that integrating religious moderation values in Islamic Religious Education learning is essential for shaping students into moderate, inclusive individuals with a balanced religious perspective. By employing appropriate strategies, schools can foster a harmonious educational environment free from intolerance.